2021
DOI: 10.1186/s40249-021-00841-4
|View full text |Cite
|
Sign up to set email alerts
|

Key Chagas disease missing knowledge among at-risk population in Spain affecting diagnosis and treatment

Abstract: Background Chagas disease is endemic in Latin America and, over the last few decades, due to population movements, the disease has spread to other continents. Early diagnosis and treatment are critical in terms of improving outcomes for those living with Chagas disease. However, poor knowledge and awareness is one of barriers that affects access to Chagas disease diagnosis and treatment for the population at risk. Information regarding immigrants’ knowledge concerning Chagas disease control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…The “economic” studies include cost-benefit analyses of screening programs [ 50 , 51 ]. The five social science [ 52 , 53 , 54 , 55 , 56 ] papers fall within anthropology, sociology and interdisciplinary teams that include anthropologists. To be clear, there are significantly more social science articles on Chagas, but only these five specifically focus on the topic of congenital Chagas or have a significant portion of the article dedicated to congenital Chagas according to our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The “economic” studies include cost-benefit analyses of screening programs [ 50 , 51 ]. The five social science [ 52 , 53 , 54 , 55 , 56 ] papers fall within anthropology, sociology and interdisciplinary teams that include anthropologists. To be clear, there are significantly more social science articles on Chagas, but only these five specifically focus on the topic of congenital Chagas or have a significant portion of the article dedicated to congenital Chagas according to our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, more than half the Bolivian participants showed poor knowledge on Chagas disease, in line with similar results published recently by Ronay-Barja et al . [ 23 ] in Madrid and other authors in Spain and Europe, who also report that most people with Chagas disease are from Bolivia [ 15 , 46 , 47 ]. This highlights the need for continuing community-based interventions in order to improve Chagas disease awareness within the population at risk.…”
Section: Discussionmentioning
confidence: 95%
“…To assess the factors associated with the participants’ level of knowledge about Chagas disease, a knowledge index was calculated according to the study published by Romay‑Barja et al [ 23 ]. To create the knowledge index, we selected five facts about Chagas disease that we considered respondents should know: it can be transmitted by triatomines [ vinchuca s (kissing bugs)] (1 point) or from mother to child (1 point); cardiac involvement is a main consequence of the disease (1 point); digestive disorders constitute the main symptom (1 point); and affected people can be asymptomatic (1 point).…”
Section: Methodsmentioning
confidence: 99%
“…This fact, together with the lack of knowledge about vertical transmission, is a very relevant aspect in non-endemic countries and is also very worrisome, because it could produce a feeling of invulnerability in non-endemic regions. In fact, previous studies showed a low knowledge about CD transmission, signs and symptoms, diagnosis and treatment in Bolivian population in non-endemic countries [ 5 , 18 , 19 , 40 42 ]. In addition, diagnosis and treatment hesitancy in children is also a relevant aspect because it is known that this population group has the best treatment outcomes and fewer side effects [ 1 ].…”
Section: Discussionmentioning
confidence: 99%